Molecular dynamics simulation study of cetylpyridinum chloride and cetyltrimethylammonium bromide micelles - Farafonov, Vladimir S.; Lebed, Alexander V. (V. N. Karazin Kharkiv National University Bulletin. Chemical series, 2016)
Properties of cetylpyridinum chloride and cetyltrimethylammonium bromide micelles were investigated by means of molecular dynamics simulation. The depth of water penetration into hydrocarbon micelle cores was inspected. The distribution and binding of counter-ions around micelles were examined. The all-atom potential models for surfactants studied were developed.